The Influence of Urban Environment on Immigrants’ Integration in Józsefváros and Kőbánya - Szalai, Boglárka (Szociológiai Szemle, 2023)
The main aim of Concordia Discors research was to investigate through the analysis of intergroup relations the effects of different urban environments on the dynamics of third-country migrants’ integration in Józsefváros and Kőbánya. A fundamental assumption of the project was that integration is a dynamic achievement, which is highly affected by the urban environment and it is neither a rigid state nor the theoretical opposite of conflict. In order to investigate the nature of intergroup relations in different urban environments a mixture of several methods was used, such as interviews, analysis of statistical data and mental mapping. From the results of our research we concluded that intergroup relations are highly influenced by the urban function (working, residential or mixed) of a particular neighbourhod. The following article aims to describe the diverse forms of coexistence of majority and minority groups in Józsefváros and Kőbánya through results of the interviews and media analysis carried out in the summer of 2011.